Inclusão no contexto escolar: estado do conhecimento, proposições e desafios - Luz, Rosângela Maria Nunes da (2017)
This dissertation focuses on the trends of scientific production about the alternatives / propositions related to Inclusive Education, taking as a source of primary data the Brazilian Journal of Special Education (RBEE), observing the temporal cut from 2005 to 2015. The work contemplates the concern of Systematizing the alternatives that have been developed and carried out within the scope of academic research, whose disclosure could contribute to qualify the practices mobilized in the current inclusive processes. In its methodological course, this study is guided by the contributions of the bibliographical research, taking as a reference41 articles published in the RBEE, in the period in question, interpellating them with questions, such as: who is producing in this area of knowledge (gender, Institutions)? What are the methodological procedures adopted in the research? In what empirical fields are these issues being addressed? What are the objects of study of the analyzed texts (typology of deficiencies)? What are the criticisms pointed out in the works for the practice of Inclusive Education? After the detailed analysis of the corpus, we obtained as a result some notes that outline a cut in the state of knowledge of the academic researches that deal with Inclusive Education in the country. Among the conclusions reached with this study, it is possible to emphasize: it is necessary the continuous acquisition of knowledge that helps in the formation of vision, posture and actions directly adjusted to the inclusive process; Inclusive school demands from all participants commitment and availability, the only way to provide students with opportunities to participate and enhance their skills; school inclusion can not become a government-imposed model that generalizes and shapes differences in similarities; Needs to be built according to the specificity of each disabled student; The notion that, without the support of society, government agencies and the entire school community, the inclusion of students with disabilities will not be realized with the necessary quality and speed, remaining as a desired, but not achieved, utopia. The study, therefore, reinforces the thesis that it is necessary to meet the special educational needs of students in a regular system of education, in order to promote learning and personal development for all who are there.